DETERMINING ACCESS TO CAPITAL, FINANCE TECHNOLOGY, FINANCIAL LITERACY, AND INTERESTS USING E-COMMERCE ON PERFORMANCE MSMES (STUDY ON SMES IN SIDOARJO DISTRICT) - Yanti, Devi; Biduri, Sarweda; Safara, Nur Amiliyah; Pratiwi , Jihan Adi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research aims to determine the influence of Access to Capital, Financial Technology, Financial Literacy, and Interest in Using E-Commerce on the performance of MSMEs in the food and beverage sector in Sidoarjo Regency. Method: This research method uses a quantitative approach with data collection techniques using questionnaires. Determining the sample in this study used the Slovin formula. The total number of respondents in this study was 81. Then for data processing using SPSS software. Results: The results of this research prove that partially Access to Capital, Financial Technology, and Interest in Using E-Commerce influence the performance of MSMEs. Meanwhile, the Financial Literacy variable was proven to have no effect on MSME performance. Novelty: This study provides empirical evidence on the role of Access to Capital, Financial Technology, and Interest in Using E-Commerce in enhancing MSME performance, while also highlighting that Financial Literacy does not significantly impact MSME performance in the food and beverage sector in Sidoarjo Regency.